The internal structure of the state protection of children in Mendoza: the actors and their movements (1995-1999) - Vitaliti, José María (AWARI, 2020)
The state protection of children in the last 30 years has a critical reflection of the ratification of the first human rights treaty for children and adolescents. Multiple glances focused on the bureaucratic normative apparatuses that operated/operate on children's bodies, to glimpse the configuration of institutional practices. This article attempts to reconstruct the circuits generated through the articulation and power networks related to the state protection of institutionalized childhood (1995 - 1999), through the study of the actors involved in the institutionalization in the province of Mendoza. The methodology used is hermeneutical, heuristic and will be carried out from the analysis of the case of the “witnesses”. For this, three cases of institutionalized boys, girls, and adolescents have been chosen, reflected in institutional files. The results raise the relevance of four institutional actors that are key in institutional actions, whose profiles could be translated into the decision-maker, the communicational control, the sentinel, and the public force. On the other hand, in the minimal networks of the cases presented, the subordination of one (executive) power over another state (judicial) power is proposed. Finally, differentiated power dynamics are indicated between the center and the peripheries of the province of Mendoza, Argentina.